Plan estratégico de marketing para el posicionamiento del centro de insumos agrícolas y veterinarios “Punto Agrícola” de la ciudad de Tulcán. - Portilla Chugá, Karina Paola (2015)
This thesis is developed based on the need of the Center for Agricultural inputs and veterinary "Agricultural Point” to achieve positioning, as it is crucial to apply the knowledge of marketing, to be applied in practice by developing strategies that will differentiate from competitors. In the theoretical framework basics of the various theoretical positions on marketing are described, the same used in the development of the proposal and give the reader a clear view of the important issues, because they consist of analysis of each concept. Within the methodological framework using quantitative and qualitative paradigms within the types of research that were used, applied research, field and descriptive literature detailing described further using research methods such as observation añd validation via experts, allowing to obtain the information necessary for the achievement of the proposal. With the development of the thesis, it is possible to determine the current situation of the Centre of agricultural inputs and veterinary "Agricultural point” of he city of Tulcán, by diagnosing failures was determined, using management tools such as SWOT, to through which competitive strategies designed. The proposal on the strategic marketing plan, strategic direction, consisting of vision, mission, principles, values, objectives and strategies focused on price, place, product, promotion and advertising, the same consisting of plans is made action indicators to assess the objective